2011
DOI: 10.1016/j.jesp.2011.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Subtle priming of shared human experiences eliminates threat-induced negativity toward Arabs, immigrants, and peace-making

Abstract: Many studies demonstrate that mortality salience can increase negativity toward outgroups but few have examined variables that mitigate this effect. The present research examined whether subtly priming people to think of human experiences shared by people from diverse cultures increases perceived similarity of members of different groups, which then reduces MS-induced negativity toward outgroups. In Study 1, exposure to pictures of people from diverse cultures engaged in common human activities non-significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 19 publications
3
40
1
Order By: Relevance
“…However, this type of effect was not observed when new laïcité was salient, and new laïcité was related, according to previous research, to less tolerance in intergroup relations. Thus, our results are consistent previous laboratory experiments (e.g., Gailliot et al 2008;Jonas et al, 2008;Motyl et al, 2011;Rothschild et al 2009) that have used the priming of reminders of attacks (or of death reminders) and shown that priming cultural values can reverse the traditional negative aggression-enhancing effects of mortality salience. Nevertheless, all of these previous studies are laboratory experiments conducted in non-life threatening conditions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, this type of effect was not observed when new laïcité was salient, and new laïcité was related, according to previous research, to less tolerance in intergroup relations. Thus, our results are consistent previous laboratory experiments (e.g., Gailliot et al 2008;Jonas et al, 2008;Motyl et al, 2011;Rothschild et al 2009) that have used the priming of reminders of attacks (or of death reminders) and shown that priming cultural values can reverse the traditional negative aggression-enhancing effects of mortality salience. Nevertheless, all of these previous studies are laboratory experiments conducted in non-life threatening conditions.…”
Section: Discussionsupporting
confidence: 91%
“…After showing that mortality salience can increase authoritarian tendencies and intergroup hostility, TMT researchers began to study variables that might curb such effects (Motyl et al, 2011). Although there are still relatively few studies, findings suggest that reminding individuals of some core aspects of their worldviews can help them cope with the threat of death (see Greenberg et al, 1992;Gailliot et al 2008;Jonas et al, 2008;Rothschild, Abdollahi, & Pyszczynski, 2009).…”
Section: Coping With Terrorism: Terror Management Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that these subjectively important similarities were experienced as threatening at some other level, perhaps to one's positive distinctiveness (as in Brown & Abrams, 1986;Gabarrot et al, 2009). On the other hand, this research forms an interesting counterpoint for the work of Motyl et al (2011) who found that similarity priming had a reductive effect on prejudice towards Arab people and immigrants because it weakened the negative, threatbased, effects of mortality salience. Other work documents the ambiguous nature of humanlevel identity and norms in shaping social discrimination and shows that emphasising shared humanity is not uniformly positive because what it means to be human can be both malevolent and benevolent (e.g.…”
Section: Discussioncontrasting
confidence: 59%
“…Elsewhere, Motyl et al (2011) found that similarity priming diminishes the negative, threat-based, effects of mortality salience on prejudice towards Arab people and immigrants. It was argued that priming widely shared human experiences attenuates threat (mortality salience) and reduces prejudice.…”
Section: Priming and Cognitive Antecedents Of Prejudice: The Role Ofmentioning
confidence: 99%